Evolution of Supraglacial Lakes on the Larsen B Ice Shelf in the Decades Before it Collapsed. Issue 4 (19th February 2020) - Leeson, A. A.; Forster, E.; Rice, A.; Gourmelen, N.; van Wessem, J. M.
Abstract: The Larsen B ice shelf collapsed in 2002 losing an area twice the size of Greater London to the sea (3, 000 km 2 ), in an event associated with widespread supraglacial lake drainage. Here we use optical and radar satellite imagery to investigate the evolution of the ice shelf's lakes in the decades preceding collapse. We find (1) that lakes spread southward in the preceding decades at a rate commensurate with meltwater saturation of the shelf surface; (2) no trend in lake size, suggesting an active supraglacial drainage network which evacuated excess water off the shelf; and (3) lakes mostly refreeze in winter but the few lakes that do drain are associated with ice breakup 2–4 years later. Given the relative scale of lake drainage and shelf breakup, however, it is not clear from our data whether lake drainage is more likely a cause, or an effect, of ice shelf collapse. Key Points: Supraglacial lakes spread southward on Larsen B ice shelf in the two decades before its collapse at a rate commensurate with meltwater saturation of its surface There was no trend in lake size during this time, suggesting an active surface drainage network that evacuated excess water off the shelf Lakes mostly refreeze in winter but a few lakes drain; those that drain seem to be associated with ice breakup 2–4 years later